Synthesis of Silylated Azauracil 1-Oxides by Metal-Free Direct Silylation - Mahato, Frenki; Ghosh, Asim Kumar; Hajra, Alakananda (Synlett, 2025)
A direct C–H silylation strategy is reported for synthesizing silylated derivatives of azauracil 1-oxide in a simple and environmentally benign way under metal-free conditions using triphenylsilane as a silyl precursor and TBHP as an oxidant. This methodology is useful for late-stage modification of various bioactive molecules, such as ibuprofen and gemfibrozil. A mechanistic investigation suggested that the reaction proceeds through a radical pathway.
Keywords: metal-free reaction; silylation; azauracil oxides; late-stage functionalization; medicinal chemistry